O enfrentamento da violência sexual contra crianças e adolescentes: o caso de uma escola da rede pública municipal de Santarém-PA - SOUSA, Andreia Riker Soares de (Universidade Federal do Oeste do Pará, 2021)
This dissertation is linked to the Postgraduate Program in Society, Environment and Quality of Life of the Interdisciplinary Training Center of the Federal University of the West of Pará (UFOPA), in the Public Policy, Diversity and Amazonian Development Research Line. The research addresses the confrontation of sexual violence against children and adolescents in a school context. The research is based on the following question: How has the researched school been facing sexual violence against children and adolescents? Based on this problem question, the general objective is to analyze actions developed by the School in the face of sexual violence against children and adolescents. Methodologically, the research is of a qualitative nature, contemplating for this purpose: techniques of documentary analysis and the accomplishment of a semistructured interview with the teachers, pedagogical coordinator and the director of the school. The analysis of the data presented, point out: 1) In the School's Political Project Pedagogical there are no official forecasts of actions to combat sexual violence. 2) The director, educator and teachers do not present specific training regarding the confrontation of sexual violence against children and adolescents. Therefore, they have a notion of the consequences of this form of violence and the importance of denunciation and due notification procedures organs of Protection to the child and to the adolescent. 3) In terms of municipality the Secretariat of Municipal Education of Santarém uses the resource "The restorative circles in the Schools". It is concluded that although the School's Political Pedagogical Project is silent on the subject, the school has been discussing the need for this theme to be based on the school curriculum.